Analysis of Acoustic Parameters of Voice Jitter and Shimmer in Children with Dysphonia after Laryngeal Surgery - Alieva, Munira Ulugbekovna; Nadzhmutdinova, Nozima Shamsutdinovna; Abdukayumov, Abdumannap Abdumazhidovich; Inoyatova, Flora Ilyasovna; Musaev, Muhammadjon Makhmudovich; Abdullaeva, Malika Ilkhamovna (Archives of Case Reports, 2025)
The article conducted a study of computer acoustic analysis of Jitter and Shimmer voice parameters in children with dysphonia after laryngeal surgery. The study found that children with dysphonia had significantly lower preoperative Jitter and Shimmer scores (574359, 587, and 2.3) compared to healthy children (1316743.376 and 4.84). At 1 month after surgery, affected children showed a decrease in Jitter and Shimmer indices compared with these acoustic indices before surgery. However, at 2 months, there was a significant increase in Jitter and Shimmer scores, and at 3 months, Jitter and Shimmer scores were comparable to Jitter and Shimmer scores in healthy children without dysphonia. The results of the study show that the method of analyzing the acoustic parameters of the voice Jitter and Shimmer allows a phoniatrist to objectively assess the occurrence of a voice disease in patients with dysphonia, and this method is the most accurate criterion for determining the pathologies of dysphonia and determining the treatment program for the disease.